Life‐history strategies in salmonids: the role of physiology and its consequences. (27th May 2021) - Birnie‐Gauvin, Kim; Bordeleau, Xavier; Cooke, Steven J.; Davidsen, Jan G.; Eldøy, Sindre H.; Eliason, Erika J.; Moore, Andy; Aarestrup, Kim
ABSTRACT: Salmonids are some of the most widely studied species of fish worldwide. They span freshwater rivers and lakes to fjords and oceans; they include short‐ and long‐distance anadromous migrants, as well as partially migratory and non‐migratory populations; and exhibit both semelparous and iteroparous reproduction. Salmonid life‐history strategies represent some of the most diverse on the planet. For this reason, salmonids provide an especially interesting model to study the drivers of these different life‐history pathways. Over the past few decades, numerous studies and reviews have been published, although most have focused on ultimate considerations where expected reproductive success of different developmental or life‐history strategies are compared. Those that considered proximate causes generally focused on genetics or the environment, with less consideration of physiology. Our objective was therefore to review the existing literature on the role of physiology as a proximate driver for life‐history strategies in salmonids. This link is necessary to explore since physiology is at the core of biological processes influencing energy acquisition and allocation. Energy acquisition and allocation processes, in turn, can affect life histories. We find that life‐history strategies are driven by a range of physiological processes, ranging from metabolism and nutritional status to endocrinology. Our review revealed that the role of these physiological processes can vary across species and individuals depending on the life‐history decision(s) to be made. In addition, while findings sometimes vary by species, results appear to be consistent in species with similar life cycles. We conclude that despite much work having been conducted on the topic, the study of physiology and its role in determining life‐history strategies in salmonids remains somewhat unexplored, particularly for char and trout (excluding brown trout) species. Understanding these mechanistic links is necessary if we are to understand adequately how changing environments will impact salmonid populations.